Evaluación de complejos húmicos edáficos sobre el comportamiento agronómico en el cultivo de arroz en Simón Bolívar, Provincia del Guayas - Mera Moncayo, Billy Nelson (2018)
VIII. SUMMARY He presents titulación work it took place in the lands of the property "San Sebastian" property of Mr. Billy Mera, located in Km 8,5 of the road Jujan - Simón Bolívar. The experimental work outlines ten treatments and three repetitions. As objective of the work it thought about the evaluation of the agronomic behavior of the rice with the application of complex humic in soil, with the purpose of finding the product and more influential dose on the yield of the cultivation. The cultivation was sowed with the variety INIAP-14 in parcels of 20 m2, distributing the treatments at random in a design of complete blocks. For the evaluation and comparison of stockings was used the test from Tukey to 5 significancia%. The evaluated variables were: height of plant, plants number or m2, grains for panicule, panicules longitude, number of panicule m2, days to flowering, days to crop, number of grains for panicule, weight 1000 seeds, yield for hectare and economic analysis. When revising the results it was found that the variables related with the yield were highly influenced by the application of Humicrop, increased in a significant way with relationship to the witness non treaty. The statistical analysis demonstrated that the complex complementary humic to the nutrition of floors, went superior to the witness, what indicates the existence of a deficit of this material in the soil. All the variables presented statistical significance, the biggest production in the cultivation was given applying Humicrop 200 kg/ha (6097,33 kg/ha). Key words: gramineous, nutrition, organic matter, cultivate, improvement.